Struktur Komunitas Hutan Mangrove Di Sungai Donan Kabupaten Cilacap, Jawa Tengah - Ashari, Desy Puspita; Muhammad, Fuad; Utami, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Mangrove forests are plant communities in coastal areas that have high productivity. The development of the Cilacap coastal area poses a threat to the degradation of the Cilacap coastal environment. The Cilacap Coast has mangrove ecosystems that grow along the Donan River but its sustainability is threatened due to mangrove forest degradation. Mangrove forest monitoring is very important to determine the current situation due to the degradation and conversion of mangrove forests. This study aims to determine the community structure of Sungai Donan mangrove forest. Determination of research location with purposive sampling method. Mangrove vegetation sampling technique uses square plot method. Mangrove vegetation analysis uses important value index of mangrove species, diversity index, dominance index and evenness index. The results of the study there were 10 species of mangroves including Aegiceras corniculatum, Avicennia alba, Bruguierra cylindrica, B. gymnorrhiza, Nypa fruticans, Rhizophora apiculata, R. mucronata, Sonneratia alba, Hibiscus tiliaceus and Terminnalia catappa. The results showed that at each station the highest importance index was Avicennia alba in the upstream of Donan river, Alas Malang and Perhutani Banyumas Barat. The highest important value index in the Cilacap Industrial Area and the Kutawaru mangrove species are Sonneratia alba and Hibiscus tiliaceus. Sungai Donan mangrove forest community has a moderate index diversity value ranging from 1.23 to 1.78, high evenness ranges from 0.89 to 0.97, and low dominance index values range from 0.18 to 0.34.